Preparation, chemical characterization and determination of the antioxidant, cytotoxicity and anti-gastric properties of plant leaf aqueous extract green-synthesized gold nanoparticles - Baoping Jiao; Zhe Bai; Jingyi Li (Journal of Science: Advanced Materials and Devices)
Gold nanoparticles (AuNPs) are known for their medical uses and have been the subject of much research. Both physical and chemical synthesis methods are employed to produce AuNPs. However, there is a growing interest among researchers globally in exploring alternative, more environmentally sustainable, and cost-effective large-scale production techniques, particularly those involving green synthesis through biological processes. This international emphasis on green nanotechnology research has caused the development of various nanomaterials that are suitable for physiologically and environmentally responsible applications. Here, gold nanoparticles were formulated utilizing the leaf of Lawsonia inermis for making the synergistic anti-gastric cancer and antioxidant effects. According to the antioxidant assay, the nanoparticles and BHT (butylated hydroxytoluene) respective IC50 values for 2,2-Diphenyl-1-picrylhydrazyl (DPPH) were 32 and 10 μg/mL. The characterization of the nanoparticles was conducted through various chemical techniques, including Fourier transform-infrared spectroscopy (FT-IR) and ultraviolet–visible spectrophotometry (UV–Vis), zeta potential, and transmission electron microscopy (TEM). The data suggested that the green-synthesized nanoparticles had an average size of 29.66 nm. The anti-human gastric cancer efficacies of the AuNPs were determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay over 48 h on both normal human vascular endothelial cells (HUVEC) and gastric cancer cells, specifically MKN45 and NCI–N87. The presence of gold nanoparticles led to a decrease in the viability of malignant gastric cells viability. The IC50 values for the nanoparticles were determined to be 113 μg/mL for the NCI–N87 cell line and 120 μg/mL for the MKN45 cell line. Following an evaluation of the efficacy of these nanoparticles in clinical trial studies, it may serve as a promising alternative to traditional chemotherapy agents.